Looking for Prophets? The Trend Receiver Approach - Jan-Diederich Lüken (Marketing Review St.Gallen, 2020)
Customer foresight strives to determine future consumer wants. One method of customer foresight is the so-called trend receiver approach. Experts who are judged as able to anticipate trends at an early stage are interviewed in a targeted and methodically guided manner. This article analyses the ambitions, prospects and restrictions of the trend receiver approach and how it can contribute to foreseeing future developments.
Keywords: 650